THE APPLICATION OF INSTAGRAM ACTIVITY TO IMPROVE STUDENTS` MOTIVATION IN ENGLISH SPEAKING - Lisa Rakhmanina; Yuneva Yuneva (Edu-Ling: Journal of English Education and Linguistics, 2018)
This study was aimed at finding out: (1) the significant difference in speaking achievement between the students who were trained with Instagram activity and those who were not; (2) the significant difference in motivation toward English Speaking between before and after the students were trained using Instagram Activity technique; (3) the interaction between teaching strategies and motivation toward students’ speaking ability; and (4) the students’ feedbacks concerning the Instagram Activity shown by the difference in students’ speaking achievement. This study applied a quasi experimental study. The instruments used to find out the data were questionnaire and tests. The calculation of the study was applying descriptive and inferential analysis. The study result showed that Instagram activity in English speaking class was applied during the process of the teaching and learning in the classroom. It showed significant different on students` English achievement from pre-test to post-test between the students with low and high motivation. It means that Instagram activity could improve students` English speaking skill and could also motivate students to learn more.